Eldecalcitol improves chair-rising time in postmenopausal osteoporotic women treated with bisphosphonates - Iwamoto J; Sato Y (Dove Medical Press, 2014)
Jun Iwamoto,1 Yoshihiro Sato21Institute for Integrated Sports Medicine, Keio University School of Medicine, Tokyo, Japan; 2Department of Neurology, Mitate Hospital, Fukuoka, JapanAbstract: An open-label randomized controlled trial was conducted to clarify the effect of eldecalcitol (ED) on body balance and muscle power in postmenopausal osteoporotic women treated with bisphosphonates. A total of 106 postmenopausal women with osteoporosis (mean age 70.8 years) were randomly divided into two groups (n=53 in each group): a bisphosphonate group (control group) and a bisphosphonate plus ED group (ED group). Biochemical markers, unipedal standing time (body balance), and five-repetition chair-rising time (muscle power) were evaluated. The duration of the study was 6 months. Ninety-six women who completed the trial were included in the subsequent analyses. At baseline, the age, body mass index, bone mass indices, bone turnover markers, unipedal standing time, and chair-rising time did not differ significantly between the two groups. During the 6-month treatment period, bone turnover markers decreased significantly from the baseline values similarly in the two groups. Although no significant improvement in the unipedal standing time was seen in the ED group, compared with the control group, the chair-rising time decreased significantly in the ED group compared with the control group. The present study showed that ED improved the chair-rising time in terms of muscle power in postmenopausal osteoporotic women treated with bisphosphonates.Keywords: osteoporosis, fall, vitamin D, muscle power, body balance